Interactional construction grammar approach to ELF:: The case of I think it is construction - Piątkowska, Katarzyna (International Journal of English Studies, 2026)
Recent discussion in linguistics indicates that English as a lingua franca can be analysed from the perspective of Construction Grammar (CxG). However, research on ELF has not focused on emerging patterns viewed as constructions. Instead, the majority of studies on spoken ELF so far have used Conversational Analysis to examine communication in ELF. Thus, in this paper spoken-language phenomena in ELF are viewed from the perspective of Interactional Construction Grammar (ICxG), which integrates CxG and Conversation Analysis. ICxG has been implemented only in research on conventional languages. The present study suggests that it can also be used in the analysis of spoken phenomena in ELF if we treat a turn as a construction. Therefore, the paper presents the results of a corpus-based study of I think it is construction in spoken ELF, demonstrating that it can be treated as a construction.